Optimizing Binder Type and Concentration to Enhance Stability and Acceptability of Pasta Feed for Swamp Eel (Monopterus albus) - Abidin, Zaenal; Lumbessy, Salnida Yuniarti; Diniarti, Nanda; Alim, Sahrul; Rahmadani, Thoy Batun Citra; Arfatunnisa (Aquaculture Department, University of Mataram, 2025)
Feed stability is a crucial factor in aquaculture, as it affects both the physical integrity of the feed and its acceptance by aquatic species. For Monopterus albus (swamp eel), maintaining feed stability while ensuring palatability is vital for optimal growth and health. This study aimed to evaluate the effects of different binder types and concentrations on the stability and acceptability of pasta feed for Monopterus albus (swamp eel). Seven binders—gelatin, gluten, CMC, chitosan, alginate, guargum, and carrageenan—were tested at 0%, 10%, 15%, and 20% concentrations using a completely randomized design. Feed disintegration and breakdown times, along with feeding behavior, were analyzed using non-parametric tests. Gelatin, CMC, and chitosan significantly improved feed stability (p < 0.05), maintaining cohesion for over 40 minutes. Gelatin at 10% concentration yielded optimal results, balancing water resistance and palatability. Behavioral observations showed that gelatin-based feeds were most preferred, with increased feeding frequency and consumption. When combined with natural attractants such as worms and snails, gelatin feeds enhanced intake rates. These outcomes indicate that protein-based binders, particularly gelatin, offer superior mechanical and nutritional advantages compared to polysaccharide alternatives. Gelatin’s dual role as a binder and nutritional enhancer provides a promising strategy for sustainable aquaculture feed development.